CFD Study of Industrial FCC Risers: The Effect of Outlet Configurations on Hydrodynamics and Reactions - Gabriela C. Lopes; Leonardo M. Rosa; Milton Mori; José R. Nunhez; Waldir P. Martignoni (International Journal of Chemical Engineering)
Fluid catalytic cracking (FCC) riser reactors have complex hydrodynamics, which depend not only on operating conditions, feedstock quality, and catalyst particles characteristics, but also on the geometric configurations of the reactor. This paper presents a numerical study of the influence of different riser outlet designs on the dynamic of the flow and reactor efficiency. A three-dimensional, three-phase flow model and a four-lump kinetic scheme were used to predict the performance of the reactor. The phenomenon of vaporization of the liquid oil droplets was also analyzed. Results showed that small changes in the outlet configuration had a significant effect on the flow patterns and consequently, on the reaction yields.